Presence of Indicator Bacteria and Occurrence of Potentially Pathogenic Nontuberculous Mycobacteria Species in Packaged Ice Cubes in Central Mexico - Oscar Castro-Morales; Ricardo Jiovanni Soria-Herrera; Gilberto Cornejo-Estudillo; Amanda Marineth Avila-Trejo; Daniel Valencia-Trujillo; Ma. Guadalupe Zanella-Vargas; Ma. Estela Vázquez-Barrios; Esmeralda Rangel-Vargas; Javier Castro-Rosas; Rocío Liliana García-Reyes; Sandra Rivera-Gutiérrez; Victoria Campos-Peña; et al. (Journal of Food Protection, 2024)
This study aimed to determine the bacteriological quality and presence of diarrheagenic Escherichia coli pathotypes (DEP) and nontuberculous mycobacteria (NTM) species in 85 packaged ice samples from 12 different states of central Mexico. Three samples had a pH of 9.8 and therefore fell outside of the acceptable range for pH. All samples were positive for aerobic-mesophilic bacteria, with limits ranging from 1 to 3.47 log CFU/mL. In total, 35, 11, and 3 ice samples were positive for total coliforms (TC), fecal coliforms (FC), and E. coli, respectively. In the samples, the TC concentration ranged from <1.1 to >23 MPN/100 mL and from <1.1 to 23 MPN/100 mL for FC and E. coli. In total, 38 (44.7%) ice samples were outside of Mexico's official guidelines. None of the 12 E. coli strains isolated from the three ice samples belonged to DEP. NTM were recovered from 20 ice samples and included M. neoaurum (n = 7), M. porcinum (n = 2), M. flavescens (n = 2), M. fortuitum (n = 1), M. abscessus (n = 1), M. senegalense (n = 1), M. conceptionense (n = 1), and M. sp. (n = 1). In the remaining four samples, two NTM were isolated simultaneously. Thus, we recommend that producers should evaluate the microbiological quality of purified water used as a raw material as well as that of the final product, the ice should be packed in thick bags to avoid stretching and tearing during transportation or storage to prevent environmental contamination of ice, personnel involved in the production, and handling of ice should be trained in relative hygiene matters and how ice-machines should be cleaned and disinfected and the implementation of hazard analysis and critical control points must be applied throughout the chain of production. Finally, regular inspection by the authorities is also of great importance. These recommendations can be applied in different countries with low microbiological quality packaged ice.